Out-of-Pocket Expenditures of Myocardial Infarction Patients in Pondicherry, South India - Chandar Sahanaa; Anil Jacob Purty; Stalin Prabakaran; Mark Christopher Arokiaraj; Manjunatha C H (Shahid Sadoughi University of Medical Sciences, 2023)
Background: Myocardial infarction (MI) is a leading cause of morbidity and mortality worldwide. In India, incidence of MI is rapidly increasing due to lifestyle changes, ageing and rising healthcare costs. The out-of-pocket expenditure (OOPE) for MI care in India can be substantial, as majority of healthcare costs are paid by patients or their families. However, little is known about the actual OOPE incurred by MI patients in tertiary care centres in Pondicherry, South India. This study aims at estimating the OPPE by MI patients attending the tertiary care centre in Pondicherry. The findings can inform policymakers and healthcare providers in developing interventions to reduce the financial burden of MI care in patients and their families. Methods: This was a hospital-based, cross-sectional study conducted on patients attending Cardiology's outpatient department OPD, who had myocardial infarction in the past for about 3 months to 3 years at the time of enrolment in the study. A pre-designed and validated questionnaire was used to collect information regarding socio-demographic details and cost of health expenditures (direct medical and non-medical costs and indirect cost for both the participants and caregivers). Data analysis was done using SPSS24 Software. The median and inter-quartile range was used for assessing the cost of health expenditures. Results: Study participants underwent invasive and non-invasive procedure as part of their management. More than 93% underwent invasive, and the cost ranges from 1,694.03 USD to 2470.00 USD (1,20,000 INR to 1,75,000 INR). They spent 10.58 USD to 21.17 USD (750 INR to 1,500 INR) for their monthly medication. The travel expenses for each follow-up visit were between 5.64 USD to 70.57 USD (400 INR and 5000 INR). The majority of participants received health insurance or reimbursement of 1834 USD (1,30,000 INR) from their firm, 12.7% of the participants  lost a payment of 162 USD to 776.28 USD (11,500 INR - 55,000 INR). Conclusion: The cost of the invasive procedure for myocardial infarction patients was 1694.03 USD to 2470.00 USD, which was the major share from the out-of-pocket expenditure compared with the other direct and indirect costs.